Employment Agreements as the Basis of Industrial Relations and the Independence of Ad Hoc Judges in Resolving Industrial Relations Disputes - Ahmad Haikal Amrullah Siregar; Ali Rahmadi Batubara; Fauzan Habib Harianja; Muhammad Faiz Al Maisi (ISNU Nine-Star Multidisciplinary Journal, 2026)
In the industrial relations system, the employment agreement serves as the main basis for establishing a legal relationship between the employer and the employee. In addition to defining the rights and responsibilities of the parties, an employment agreement is an important tool for resolving and resolving problems in the employment relationship. However, open bargaining positions between employers and employees often result in disputes that ultimately require legal action. An objective and independent industrial relations tribunal with ad hoc judges who are experts in the field of employment is needed to resolve these issues. In addition to examining the independence of ad hoc judges in the process of resolving industrial relations failures, this study seeks to investigate the position of employment agreements as the basis of industrial relations. Normative juridical research with regulatory and contextual approaches is the methodology used. The findings suggest that while the independence of ad hoc judges is critical to ensuring impartial and fair adjudications, clearly structured and fair employment agreements can reduce irregularities. Therefore, in order to provide legal certainty and justice in industrial relations, employment agreements must be strengthened and the independence of ad hoc courts must be upheld.